VINYL CHLORIDE-BASED RESIN COMPOSITION - YUKITOMI MASUO; NARA SHIZUO (1992)
PURPOSE:To obtain the subject composition, containing a mixed product of a zinc compound with a piperidyl group-containing compound and a phosphoric acid compound in a vinyl chloride-based resin and excellent in water whitening, weather and heat resistances without causing zinc burn and coloring. CONSTITUTION:The objective composition containing (B) 0.1-5 pts.wt. zinc compound (e.g. a 1-22C aliphatic carboxylate) and (C) 0.01-5 pts.wt. product obtained by mixing (i) a compound [e.g. a compound expressed by the formula (R1 is H, 1-4C alkyl, 2-4C hydroxyalkyl or 2-4C acyl; R2 and R3 may form alkylenedioxy group each substituted with a monofunctional organic group such as acyloxy group or substituted amino group)] having at least one piperidyl group with (ii) one of at least phosphoric acid, an organic phosphoric acid ester, phosphorous acid and an organic phosphorous acid ester and/or an organotin compound in (A) 100 pts.wt. vinyl chloride-based resin.